Acute kidney injury after lung cancer surgery: Incidence and clinical relevance, predictors, and role of N-terminal pro B-type natriuretic peptide. (September 2018) - Cardinale, Daniela; Cosentino, Nicola; Moltrasio, Marco; Sandri, Maria Teresa; Petrella, Francesco; Colombo, Alessandro; Bacchiani, Giulia; Tessitore, Adele; Bonomi, Alice; Veglia, Fabrizio; Salvatici, Michela; Cipolla, Carlo M.; et al.
Highlights: In lung cancer surgery, acute kidney injury (AKI) relevance has not been fully studied. In our study, 10% of patients had AKI and a more complicated clinical course. AKI risk can be predicted by the combined evaluation of creatinine and NT-proBNP. Abstract: Background: Acute kidney injury (AKI) frequently occurs in several medical and surgical settings, and it is associated with increased morbidity and mortality. In patients undergoing lung cancer surgery, AKI has not been fully investigated. We prospectively evaluated the incidence, clinical relevance, and risk factors of AKI in patients undergoing lung cancer surgery. Moreover, we estimated the accuracy of N-terminal pro-B-type natriuretic peptide (NT-proBNP) in the prediction of AKI. Methods: Patients undergoing lung cancer surgery were included in the study. Plasma NT-proBNP was measured before and soon after surgery. Postoperative AKI was defined according to the Acute Kidney Injury Network (AKIN) classification. Results: A total of 2179 patients were enrolled. Of them, 222 (10%) developed AKI and had a more complicated in-hospital clinical course (overall complication rate: 35% vs. 16%; P < 0.0001), and a longer hospital stay (10 ± 7 vs. 7 ± 4 days; P < 0.0001). The incidence of AKI increased in parallel with the extent of lung resection. Among the independent predictors of AKI, serum creatinine (area under the curve [AUC] 0.70 [95% CI 0.67-0.74]) and NT-proBNP (AUC 0.71 [95% CI 0.67-0.74]) provided the highest predictive accuracy, and their combination further significantly improved AKI prediction (AUC 0.74 [95% CI 0.71-0.77]). No difference in AKI prediction was observed between preoperative and postoperative NT-proBNP (P = 0.84). Conclusions: Acute kidney injury occurs in 10% of patients undergoing lung cancer surgery, and it is associated with a high incidence of postoperative complications. The risk of AKI can be accurately predicted by the combined evaluation of preoperative serum creatinine and NT-proBNP.